Teknik Produksi dan Nilai Finansial Madu Hutan Sialang di Kelurahan Pelalawan Kecamatan Pelalawan Kabupaten Pelalawan: Production Techniques and Financial Value of Sialang Forest Honey in Pelalawan Village Pelalawan District Pelalawan Regency - Airlangga, M Sadaad; Falah, M. Darul; Suwadji, Siman (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
Non-Timber Forest Products is currently a new prospect and hope that continues to increase, where HHBK is considered to be the core of the utilization of forest products that can simultaneously preserve forests in general. One of the Non-Timber Forest Products is honey, where honey can produce financial value so as to reduce the level of dependence of the community on forest products in the form of wood. The types of honey in the forest are very diverse, one type of honey that has a high economic value is sialang forest honey. To determine the economic value of sialang forest honey is necessary to do a financial analysis through the pattern of production conducted by the community in producing the product, so that it can be known whether the business is feasible or not to do this research was conducted in the District of Pelalawan, Pelalawan regency with qualitative methods consisting of interviews and direct observation in the field. Based on the results of the study, it was found that the financial value obtained by Sialang forest honey business owners in one year was Rp74, 905, 200.00., while the income Sialang Forest Honey Harvester in one year amounted to Rp86, 514, 000.00.